The Impact of Self-Management Abilities, Sleep Quality, and Anxiety on the Well-Being of Patients With Benign Prostatic Hyperplasia: A Cross-Sectional Analysis - Shu Lingzhi MD; Hongchen Zhang PhD; Yuhong Luo PhD (Journal of Patient Experience)
Current benign prostatic hyperplasia (BPH) management prioritizes urological symptoms while neglecting psychological impacts on subjective well-being (SWB). Although chronic disease-SWB associations are established, limited evidence exists regarding interactive effects of psychosocial factors (sleep, anxiety, self-management) in BPH populations. This multicenter cross-sectional study enrolled 412 BPH patients from 6 tertiary hospitals in Northwest China. Validated instruments assessed key variables: Pittsburgh Sleep Quality Index for sleep quality, Self-Rating Anxiety Scale for psychological distress, Memorial University of Newfoundland Happiness Scale for SWB, and Chinese Self-Management Ability Scale for behavioral competencies. Structural equation modeling elucidated pathway relationships. Of the patients, 72.5% experienced sleep disorders, and 79.0% reported anxiety. Regression analysis indicated that income (β = 1.378, P  < .01) and self-management abilities (β = 0.074, P  < .01) positively impacted SWB, while anxiety (β = −0.155, P  < .01) and sleep disorders (β = −0.581, P  < .01) negatively affected it. The structural equation model revealed a direct effect of self-management abilities on SWB of 0.20 and an indirect effect of 0.16. This study contributes to the field by proposing a comprehensive, patient-centered model of care that can improve both the quality of life and long-term outcomes for BPH patients.